In Vivo Evaluation of Ecoenzyme as a Natural Bioinsecticide Against Tenebrio Molitor Larvae - Pratiwi Soesilawati; Rafael Gerrard; Yoakim Leok Taboy; Agatha Sherly Ivana Dewi; Aurelia Graceilla Putri Nindyatama; Moses Amadeus Soetanto (Universitas Airlangga, 2025)
Introduction: Organic kitchen waste fermented into eco-enzyme contains organic acids and secondary metabolites with insecticidal potential. We hypothesized that intermediate dilutions would yield higher larval mortality than very low or undiluted solutions by maximizing uptake while limiting rapid deterrence or detoxification responses. Methods: Eco-enzyme was produced from kitchen residues and brown sugar through 90-day fermentation and confirmed to contain acetic acid, lactic acid, flavonoids, and alkaloids (pH 3.0). A randomized design tested five dilutions (0%, 25%, 50%, 75%, 100%) and a chemical insecticide control (Curacron 500 EC). Each treatment had three replicates of 10 Tenebrio molitor larvae (n=180). Solutions were sprayed twice daily for seven days, and mortality recorded before each application. Data were analyzed using Shapiro–Wilk tests and one-way ANOVA (α=0.05). Results and Discussion: Phytochemical screening verified organic acids and bioactive metabolites. By Day 7, cumulative mortality was: control 23.33%, 25% eco-enzyme 46.67%, 50% 13.33%, 75% 30.00%, 100% 33.33%, and chemical insecticide 86.67%. The 25% group showed normal distribution and significantly higher mortality than several other eco-enzyme treatments (p<0.05). This intermediate concentration permitted ingestion and disruption of gut pH, digestive enzymes, and neural pathways, whereas higher concentrations provoked irritation and avoidance, reducing toxin uptake. Conclusion: Eco-enzyme at 25% provides optimal larvicidal activity, highlighting its potential as a biodegradable, low-cost alternative. Its application could support integrated pest management, lowering environmental residues, and promoting sustainable agriculture. Future work should include field validation, non-target assessments, and formulation strategies to enhance stability and scalability.